Effects of low-dose, short-duration periods of asymmetric radiation on colony formation of C6 glioma cell cultures: Fractionation has its separate additional effect - Karaman , Şule; Özben , Seda Güler; Kesen , Nazmiye Dönmez; Karaçay , Özge; Sakin , Nergiz Dağoğlu; Dizdar , Yavuz (Journal of Surgery and Medicine, 2022)
Background/Aim: Previous studies on fractionation in radiation therapy have been mainly based on applying equal doses over at least 6 h. The main purpose of fractionation is to increase normal tissue tolerance rather than tumor sensitivity. Thus, one can apply higher doses to the tumor. In contrast, new molecular studies indicate that high and low doses of radiation act by different mechanisms. This study was conducted to investigate the radiobiological effect of asymmetrical radiation doses. Methods: This is an experimental study done in vitro with a G6 glioma cell line to investigate the responses when C6 glioma cells are irradiated with single doses of 30 and 230 cGy using an orthovoltage therapy device or doses split into 30 and 200 and 115 and 115 cGy within periods of 15 and 30 min. A total of 5 × 103 cells were transferred to polyethylene culture flasks for colony formation. A cluster containing more than 30 cells was considered a new colony. Results: A single dose of 230 cGy caused a 56.8% reduction in colony formation. However, when 230 cGy was divided over 15- and 30-min periods in fractions of 30 and 200 cGy, colony formation was significantly reduced compared to the control group (68.13% and 52.64%, P = 0.030, respectively). This effect continued when the radiation dose was divided into equal fractions (115 and 115 cGy) with periods of 15 and 30 min (42.60%, P = 0.021 and 20.77%, P = 0.008, respectively). Conclusion: According to these results, (i) short interval (15 and 30 min) fractionation significantly reduces colony formation compared to a single equal dose; and (ii) the protective mechanisms activated in cell response probably vary at different radiation doses and different fractions.